1H/2H and azide/tetrazole isomerizations and their effects on the aromaticity and stability of azido triazoles1. Issue 13 (14th February 2015) - Yang, Junqing; Gong, Xuedong; Wang, Guixiang
<x xml:space="preserve">Abstract</x> DFT studies on NAzTA, AAzTA, and AzTA show –NH2 facilitates but –NO2 impedes 1H/2H tautomerization. AZ/TZ isomerization of molecules with –N3 only is the easiest. 1H/2H tautomerization decreases while AZ/TZ isomerization increases the stability.